Driving Innovation-Driven Growth in Vietnam: Effects of Digital Transformation, Foreign Direct Investment, and Human Capital on Resource Dependence (Marketing i Menedžment Innovacij)
Environmental pollution and resource curses represent significant challenges for humanity and are continuously increasing in many countries, including Vietnam. From an economic perspective, the resource curse refers to the paradoxical situation in which countries rich in natural resources tend to have slower economic growth and lower levels of development than those not rich in natural resources. There are many causes of the resource curse, but the most prominent is still the impact of economic activities, institutional quality, investment and the distribution of natural resources for industry sectors. This paper aims to investigate the role of digital transformation, foreign direct investment, and human capital in diminishing reliance on natural resources in Vietnam from 1990–2018. By applying two novel estimation methods, namely, quantile regression and the quantile‒quantile approach, the findings are summarized as follows: (i) a substantial implementation of digital transformation is necessary for Vietnam's economic growth to reduce its dependence on natural resources; (ii) foreign direct investment contributes to Vietnam's economic growth by reducing resource dependence; and (iii) the relationship between human capital and the extent of resource dependence in Vietnam's economic growth is not clearly delineated. Based on these findings, we suggest that the Vietnamese government should be consistent and further accelerate the process of digitizing the economy. Specifically, it is necessary to encourage individuals, organizations and businesses to promote the integration of digital technologies into many economic sectors, such as agriculture, health, education, and transportation. In addition, Vietnam should comprehensively evaluate and selectively attract foreign direct investment. To do this, foreign direct investment management agencies need to actively promote strategic partnerships. Accordingly, large multinational enterprises with capital and modern technology should be proactively invited to invest instead of calling in a scattered manner. In addition, it is necessary to support businesses in technological innovation, gradually participating in the supply chains of large corporations to gain management experience and could access advanced technologies worldwide.